Regulatory Effects of Companion Plants (Maize (Zea mays) and Perilla frutescens) on American Ginseng Growth and Microbiome in Root Rot-Infested Field - Dan Luo; Dengqun Liao; Tingting Han; Changhao Ji; Chao He; Xianen Li (Plants, 2025)
American ginseng (AG) cultivation suffers from severe diseases, requiring heavy pesticide use. This study aimed to explore whether companion planting with maize (AG-maize) or Perilla frutescens (AG-perilla) could enhance AG growth and alter rhizosphere/root microbiomes in a root rot-infested field. Compared to monoculture (CK), companion planting significantly improved AG growth and survival rate at wither stage, with AG-maize showing the superior efficacy- increasing root length and fresh weight, and plant height by 39.04%, 46.10%, and 48.69%, respectively, while raising survival rate from 1.51% to 14.54%. Microbial analysis revealed that companion planting increased microbiome diversity and network complexity. At green fruit stage, AG-perilla increased rhizosphere fungal Chao1 index by 42.6%, while AG-maize and AG-perilla elevated endophytic fungal Shannon indices by 46.68% and 74.84%, respectively. At wither stage, AG-maize notably enriched beneficial microbes (e.g., soil Pseudomonas +108.49%, Bacillus +200.73%) while reducing pathogens (soil Fusarium −20.04%, root endophytic Alternaria −54.55%). Structural equation model indicated AG-maize improved AG survival via core species-driven antibiosis and nutrient regulation, with keystone species Lysobacter sp. RHLT3-4 and Verrucomicrobium sp. IMCC25902 significantly correlating with AG health. The AG-maize system fostered synergistic microbial networks, enriching beneficial taxa and suppressing pathogens. These findings provide a foundation for developing eco-friendly disease management and high-yield AG cultivation strategies.